Rancangan Sistem Dalam Pengelolaan Data Penduduk Pada Kantor Desa Boloak Menggunakan Algoritma Sequential Searching - Shofia Qitala; Saruni Dwiasnati (LPPM Universitas Potensi Utama, 2023)
Fast and accurate information will support the smooth operation or management of the village government, in managing community data and information. Currently, various administrations and data management at the Boloak village office are still being carried out manually, and have not been computerized so that the performance in managing population data is still not optimal. For this reason, in utilizing information technology for managing population data and assistance data, an information system design is needed for the scope of the alternating village office, so that it can support smooth operations and improve performance for village government employees. With the aim of this research being to design a population data management system and assistance data by implementing a web-based Sequential Searching Algorithm using php and using the MySql database, this research will be designed using the waterfall method, making it easier for employees to search population data, identify population data as well as in managing social assistance data more efficiently and improving the performance of village officials in managing data.